Halal and Safe Food In Islamic Law - Tahir, Palmawati; Muslih, Muhamad (Faculty of Law, Universitas Pattimura, 2023)
The purpose of this research is to analyze and provide information to the public and to lawmakers that food is a primary need for every human being in terms of the halalness and safety of its products, it is a mandatory requirement for every consumer, especially Muslim consumers. Halal Food in Islamic Law explains about Halal Food or halal food in terms of aspects of Indonesian jurisprudence and Islamic law in Indonesia. Indonesia, which is a country with a predominantly Muslim population and is known for its very religious society, of course pays great attention to Islamic aspects in consuming food, namely halal food, both local production and imports from neighboring countries. The perspective of the basics of Islamic Law and Indonesian Law, especially regarding certification and labeling in the international trading system must receive strict attention in order to provide protection for Muslim consumers around the world, as well as a strategy to face the challenges of globalization. Lawmakers in Indonesia have made regulations related to this, namely Law Number 33 of 2014 concerning Guarantees for Halal Products (UUJPH). The method used in this study is using normative juridical methods by collecting data or information through library research, namely research conducted through literature studies via the internet and so on which are appropriate or have relevance to the problem being discussed. The results of this study state that the issue of halal and haram is very important and very urgent to be considered by all parties. The production chain from business actors to consumers is a concrete manifestation that must receive consumer protection by the state.